Laparoscopic Nephrotomy to Removal of Staghorn Calculus in a Canine - Feranti, João Pedro Scussel; de Oliveira, Marília Teresa; Pastore, Luciane Laux; Hartmann, Hellen Fialho; Linhares, Marcella Teixeira; Chaves, Rafael Oliveira; Corrêa, Luis Felipe Dutra; Brun, Maurício Veloso (Acta Scientiae Veterinariae, 2016)
Background: Renal urolithiasis is the third most common disease of the urinary tract of dogs. In humans, staghorn lithiasis affects 1 to 1.5% of the population, often women over 50 years old. In veterinary medicine, this type of lithiasis has been little reported, and there are few descriptions of treatment, both in small and large animals. The objective of this work is to report a rare case of renal staghorn stones treated by laparoscopic nephrotomy. Case: A six-year-old female schnauzer with 6 kg body weight was evaluated clinically in order to spay. According to the owner, the animal showed polydipsia. Additional tests such as blood count, serum biochemistry, radiography and abdominal ultrasound were done, showing hematological examinations within the standards for the species. After the ultrasound we noticed an asymmetric kidneys with the right kidney with preserved cortical layer and hyperechoic line corticomedullary interface, with posterior acoustic shadow and left kidney with relative/corticomedullary differentiation and pelvis preserved without alteration; this evocative image of kidney stones in kidney right. In abdominal radiographs was possible to visualize radiopaque mass in the right kidney compatible with renal staghorn stones. Excretory urography was done, which demonstrated evident excretion of contrast material in the left kidney and the right kidney doubtful. Based on these findings, we opted for exploratory laparoscopy followed by laparoscopic nephrectomy or nephrotomy for removal of urolithiasis, depending of the lesions visualized during the procedure. All procedure were performed using a minimally invasive approach without the need for conversion to open or videoassisted procedures. The most complex and delicate step was the nephrorrafy, due the little time for suturing to avoid renal ischemia. Eight months after the surgery, the owner is contacted, and it said that the animal was well, without clinical signs of kidney disease. After returning and performing ultrasound and excretory urography revealed that the right kidney had atrophied, but there was still draining contrast shown by excretory urography. Discussion: Although the use of laparoscopy is increasing worldwide is still considered an underexplored approach to renal calculi in veterinary medicine. Our choice in this case was due the numerous potential advantages that have minimally invasive compared to open technique, as demonstrated in medicine and veterinary medicine studies. At the beginning of laparoscopy was possible to elect the procedure (nephrectomy or nephrotomy) to be performed; the anatomic changes presente as renal artery patency /coloring kidney and wrist, observed by laparoscopic visualization, with amplification, showed the possibly of renal preservation. This is an advantage associated with videosurgical access. Laparoscopic view allowed to discard residual gallstones as well as to promote the correct synthesis of renal tissue. All steps of the nephrotomy were performed by minimally invasive access. It was not possible to directly correlate with the histological analysis technique renal disorder before and after the surgery, because the kidney was already reduced in size in the first operation and biopsy was not done in that occasion. The present report demonstrates that laparoscopic surgery can be considered viable for the management of renal staghorn stones in dogs. Keywords: surgery, nephrolity, canine.